Understanding Anorexia and Eating Capability of Older Adults in Attempt to Prevent Malnutrition - Afifah Amatullah; Roza Mulyana (HM Publisher, 2022)
Because of the rise of life expectancy, the older adults are now a big part of world’s population. In United States, prevalence of adults aged more than 65 years old increased from 36.6 million in 2005 to 47.8 million in 2015. In Indonesia, percentage of older adults increased two-fold from 1971 – 2019 as much as 9,6% or more than 25 million people. Along with this aging population, eating problems and malnutrition are getting more frequent. Aging causes several changes and degradation of body function which physiologically lead to anorexia and eating difficulty in older adults. Moreover, the other age-related factors such as social factor, economic factor, psychological factor, diseases and polypharmacy also have significant impact on food intake in older adults. Prevalence of inadequate energy intake and malnutrition in older adults are increasing, which lead them to become susceptible to acute and chronic diseases or worsening of their disease, increase hospitalization, and increase mortality rate. Even so, the signs of malnutrition of older adults are often late to be recognized, whereas the recovery of malnutrition in older adults is much more complicating than in younger adults. This review discusses about problems encountered by older adults that decrease their intake and cause malnutrition, to help clinicians recognize the cause of malnutrition in older adults earlier.